Identification of Quantitative Trait Loci for Tissue Culture Amenability Traits in a Dura X Pisifera F1 Oil Palm Population - Ting, Ngoot Chin (2006)
Tissue culture is employed for the large scale production of elite planting materials in the oil palm plantation industry of Malaysia. The advantage of this technique is the homogeneous quality that can be produced across the clones. However, the production cost is high compared to conventional seedlings due to some unpredictable constraints. One of the major problems that has been reported is the average low rate of regeneration among the clones. Inconsistencies have been reported in that both callogenesis and embryogenesis varied among the lines. Attempts were made to generate restriction fragment length polymorphism (RFLP) and amplified fragment length polymorphism (AFLP). These DNA markers were used for constructing genetic linkage maps for two commercial palms namely, Ulu Remis Deli dura (ENL48) and Yangambi pisifera (ML161). Both maps were used as frameworks to detect quantitative trait loci (QTL) associated with the traits of tissue culture amenability. The generation of DNA markers involved the genotyping of 87 F1 palms using 70 cDNA probes and 16 EcoRI/MseI and 8 PstI/MseI primer-pairs. This produced a total of 36 RFLPs and 43 AFLPs for ENL48 and 66 RFLPs and 58 AFLPs for ML161. The data were integrated into the existing database for the mapping analysis by using JoinMap®3.0 at LOD 4.0 and recombination frequency θ <0.400. The ENL48 linkage map was constructed by using 87 RFLPs and 123 AFLPs. These markers were grouped into 25 linkage groups covering a total genetic distance of 1,136.3cM. A denser map of ML161 was obtained with 147 RFLPs and 225 AFLPs which resulted in 16 linkage groups with a total map length of 1,755.7cM. The QTL for tissue culture amenability were determined using interval mapping and multiple quantitative mapping (MQM) with the help of the MapQTL® 4.0 software. The LOD thresholds were estimated using the permutation test. The QTLs for the callusing rate (CR) were detected at linkage groups D9 and P7 on the ENL48 and the ML161 maps, respectively. For embryogenesis rate (Er_ex), QTL was only detected on the ML161 genetic map at linkage group P13. All the detected QTLs were confirmed in a second experiment where the tissue culture data was collected using different media compositions. These improved confidence in the QTLs detected for tissue culture amenability.